2017
DOI: 10.3390/molecules22122083
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein Lipase Expression in Chronic Lymphocytic Leukemia: New Insights into Leukemic Progression

Abstract: Lipoprotein lipase (LPL) is a central enzyme in lipid metabolism. Due to its catalytic activity, LPL is involved in metabolic pathways exploited by various solid and hematologic malignancies to provide an extra energy source to the tumor cell. We and others described a link between the expression of LPL in the tumor cell and a poor clinical outcome of patients suffering Chronic Lymphocytic Leukemia (CLL). This leukemia is characterized by a slow accumulation of mainly quiescent clonal CD5 positive B cells that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…LPL, catalyzing the hydrolysis of TG into FFA, was found aberrant expression in CLL cells, which was similar to fat and muscle cells on signatures. It mediates the uptake of cholesterol, therefore reduces the level of cholesterol, HDL, VLDL, and TG (14,17,(50)(51)(52)(53). For this reason, the inhibition of STAT3 pathway is likely to inhibit the utilization of FFA in CLL cells.…”
Section: Discussionmentioning
confidence: 99%
“…LPL, catalyzing the hydrolysis of TG into FFA, was found aberrant expression in CLL cells, which was similar to fat and muscle cells on signatures. It mediates the uptake of cholesterol, therefore reduces the level of cholesterol, HDL, VLDL, and TG (14,17,(50)(51)(52)(53). For this reason, the inhibition of STAT3 pathway is likely to inhibit the utilization of FFA in CLL cells.…”
Section: Discussionmentioning
confidence: 99%
“…LPL plays a critical role in lipid metabolism (42). Studies have shown that LPL may regulate metabolic pathways to provide additional energy for cancer cells (43,44). Circulating LEP is usually secreted by white adipose tissue and is involved in the regulation of angiogenesis, energy balance, and immune and inflammatory responses (45).…”
Section: Discussionmentioning
confidence: 99%
“…Given the lack of strategies for early detection of ovarian cancer and consequent poor patient prognosis, investigating genes upregulated throughout E2-induced dysplasia formation may inform development of diagnostic and prognostic markers for E2-driven and -responsive tumours. Igfbp5 [ 38 – 40 ], Enpp2 [ 41 ], Ctsh [ 42 , 43 ], Lpl [ 44 , 45 ], and Tacc1 [ 46 – 48 ] are the top five genes correlated with the E2 branch in pseudotime and all are currently under investigation as cancer biomarkers. Preliminary studies in various human pathologies have demonstrated that IGFBP5 [ 49 ], ENPP2 [ 50 ], ENPP2 metabolites [ 44 ] and LPL [ 44 ] are secreted factors detectable in serum.…”
Section: Discussionmentioning
confidence: 99%